A dinâmica pulsional na surdez congênita ou precoce: reflexões sobre língua materna e língua de sinais - Vieira, Camila Campos Curcino (2019)
This dissertation aimed at understanding the mother tongue role in the psychological constitution of the deaf subject inserted in a family of listeners, pointing out the particularities of the lack of access to sound and the use of sign language in the early years of childhood. Our propositions were based on the analytical work with two deaf children and the elaboration of a metapsychological essay. Questions arose due to the meeting of oral language and sign language to the singularity of the drive dynamics between the object voice and transfer. We understood mother tongue as close to lalangue, that is, what is meaninglessness of the language and what escapes representation. Sign language occupied two positions in the sessions, the lalangue position itself and its elocubration, with effects of estrangement and appeasement, respectively. In the absence of sonority and in the fragility of the symbolic place occupied by the primordial Other, the object gaze became an unbearable presence or assumed a puzzled position, in which the subject was captured and there was no room for questioning knowledge. Sign language, as well as oral language, assumed the role of wrapping the object voice when used by a listening mother. Regarding deaf subjects, the place of the Other as a treasure of signifiers found boundaries when the sign language, before the maternal gaze, assumed its symbolic and instrumental potentialities to transmit desire.